2-Farthest orthogonality in generalized 2-normed spaces - Mazaheri, Hamid; Abad, Mousavi Shams; Dehghan, M. A. (Journal of the Indonesian Mathematical Society, 2018)
In this paper, we consider the concepts 2-farthest orthogonalityin generalized 2-normed spaces, We obtain a necessary and coecient conditionsfor 2-remotal sets and 2-uniquely remotal sets in generalized 2-normedspaces.